Response of Important Tropical Tree Species to Elevated CO2 - Varadharajan, S.; Buvaneswaran, C.; Warrier, Rekha R.; Jayaraj, R. S. C. (Indian Forester, 2010)
Global warming plays a major role in climate change which is caused mainly due to increase in CO2 level in the atmosphere. Present study attempted to evaluate four important tropical tree-species, Tectona grandis, Ailanthus excelsa, Casuanna equisetifolia and Casuarina ,Jungkuhniana for adaptation to elevated levels of CO2 at nursery stage. The study was conducted inside the poly tunnels and CO2 enrichment was done to double the concentration. Seedlings in poly tunnel without CO2 enrichment served as control The short term experiments revealed that of the four species studied, casuarinas performed well under elevated CO2 conditions in terms of all growth parameters studied. The performance of teak alone was poor indicating adverse effect of CO2 enrichment on morphological traits of tbiB species as seen by reduced leaf area, lesser dry' matter accumulation both in shoot and root system and poor Seedling Quality Index at elevated CO, levels. Thus, in the present study, all the species except teak showed a positive response to CO2 enrichment in terms of morphological traits while Cuuarina equisetifolia and C. junghuhniana showed better growth and seedling quality indicating their better adaptability to elevated CO2level.